2018
DOI: 10.3389/fpsyg.2018.01549
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Posttraumatic Stress Disorder Symptoms and Posttraumatic Growth in an Epidemiological Sample of Chinese Earthquake Survivors: A Latent Profile Analysis

Abstract: Background: Posttraumatic stress disorder (PTSD) and posttraumatic growth (PTG) are different psychological outcomes triggered by exposure to extraordinarily traumatic events. In this study, we aimed to examine patterns of co-occurrence between DSM-5 PTSD symptoms and PTG, among natural disaster survivors, and to clarify whether empirically-based subgroups differed by several specific predictors.Methods: Latent profile analysis was used to examine patterns of self-reported PTSD symptoms and PTG in an epidemiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
52
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 59 publications
(90 reference statements)
9
52
4
Order By: Relevance
“…This study did not identify a high PTSS/mild PTG pattern among Chinese BC patients, which was inconsistent with previous research with BC patients from other cultures . However, this result was consistent with similar research conducted among disaster survivors in China . The patterns of PTSS and PTG vary across different types of traumatic events .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This study did not identify a high PTSS/mild PTG pattern among Chinese BC patients, which was inconsistent with previous research with BC patients from other cultures . However, this result was consistent with similar research conducted among disaster survivors in China . The patterns of PTSS and PTG vary across different types of traumatic events .…”
Section: Discussioncontrasting
confidence: 99%
“…A few previous studies have explored posttraumatic response patterns using LPA. Three of these studies conducted LPA to identify the patterns of PTSS and PTG among earthquake survivors . They found similar three‐class patterns of PTSS and PTG, characterized by mild PTSS/high PTG, mild PTSS/ mild PTG, and high PTSS/high PTG.…”
Section: Introductionmentioning
confidence: 99%
“…Their narratives contained more references to positive emotions than to negative emotions. This result supports previous studies showing that there is a greater number of people who report experiencing more PTG than PTD than those who report experiencing mostly negative changes in the aftermath of trauma (e.g., Chen and Wu, 2017; Kroemeke et al, 2017; Cao et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…They found three clusters: a growth class (high on PTG, low on PTSD symptoms), a “resilient” class (low on both PTG and PTSD), and a symptom and growth class (high on both PTSD and PTG). These same classes were identified in two other studies undertaken with bereaved and non-bereaved adult ( Cao et al, 2018 ) and child and adolescent survivors of the earthquake ( Chen and Wu, 2017 ). Overall, these studies are consistent with previous PTSD literature indicating that PTG may be experienced with or without ongoing distress following trauma.…”
Section: Introductionsupporting
confidence: 57%
“…Another purpose of the study is to explore predictors of different classes. Predictors to depression and anxiety after the death include gender, educational level, negative self-perception, avoiding attachment style and low social support ( Nickerson et al, 2014 ; Boelen et al, 2016 ; Lenferink et al, 2017 ; Maccallum and Bryant, 2018 ), In terms of studies adopting LCA or LPA, social support ( Chen and Wu, 2017 ; Cao et al, 2018 ), exposure to the trauma and relationship to the deceased ( Zhou et al, 2018a , b ) are found to differentiate PTG class from other classes. We included these loss-related and socio-demographic variables as predictors of subgroup membership in our analysis.…”
Section: Introductionmentioning
confidence: 99%